Mesenchymal Stem Cells: An Overview of Their Potential in Cell-Based Therapy for Diabetic Nephropathy - Yan Wu; Chunlei Zhang; Ran Guo; Dan Wu; Jiayi Shi; Luxin Li; Yanhui Chu; Xiaohuan Yuan; Jie Gao (Hindawi Limited, 2021)
Diabetic nephropathy (DN) is a devastating complication associated with diabetes mellitus, and it is the leading cause of end-stage renal diseases (ESRD). Over the last few decades, numerous studies have reported the beneficial effects of stem cell administration, specifically mesenchymal stem or stromal cells (MSCs), on tissue repair and regeneration. MSC therapy has been considered a promising strategy for ameliorating the progression of DN largely based on results obtained from several preclinical studies and recent Phase I/II clinical trials. This paper will review the recent literature on MSC treatment in DN. In addition, the roles and potential mechanisms involved in MSC treatment of DN will be summarized, which may present much needed new drug targets for this disease. Moreover, the potential benefits and related risks associated with the therapeutic action of MSCs are elucidated and may help in achieving a better understanding of MSCs.